Risk factors of morbidity among construction workers: a review - S., Gopalakrishnan; P., Mohan Kumar (International Journal Of Community Medicine And Public Health, 2020)
Construction industry is the second largest employer of workers the world over and is second only to the number of workers in the agricultural sector. Since construction industry and workers come under the un-organized sector, they are not benefitted by any of the advantages enjoyed by the workers in the organised sector. Most of the workers belong to the poor socioeconomic background and illiterates who are hired by the agents based on the construction manpower needs on a daily wages manner. Migrant workers from poorer and under developed areas of the country are increasingly being exploited for this purpose. The rigorous and strenuous construction work and their temporary and shabby living conditions make them vulnerable for several types of diseases and ill health, for which they may not get adequate and timely medical care and support. Workplace safety and workers safety are often compromised. They constantly face physical, chemical and biological risk factors. Risk factors and risk behaviour like smoking, tobacco use, alcoholism and even substance abuse among the construction workers contribute to their high morbidity and even mortality. This review article focuses on the various risk factors and the risk behaviours, which the construction workers are exposed and are prone to develop, leading to different types of morbid conditions at the work place as well as in their places of living.